A genetic epidemiological study in British adults and older adults shows a high heritability of the combined indicator of vitamin B12 status (cB12) and connects B12 status with utilization of mitochondrial substrates and energy metabolism - Dalmia,A; Dib,M-J; Maude,H; Harrington,DJ; Sobczyska-Malefora,A; Andrew,T; Ahmadi,KR (The Journal of Nutritional Biochemistry, 2019)
Vitamin B12 deficiency is common among older adults. However, the most commonly used marker of deficiency, total serum vitamin B12 (B12), is not sensitive enough to diagnose true deficiency in a significant proportion of the population. The combined indicator of B12 status (cB12), formulated as a composite score of various biomarkers of vitamin B12 status (which also accounts for low folate status and age) has been shown to offer a more robust and powerful test to diagnose B12 deficiency.There are no epidemiological studies of cB12 variability in older adults. We carried out a twin study to characterize the relative contribution of heritable (h2) and environmental factors to the observed variability in cB12 score in an adult and older adult population (n=378). Furthermore, we tested for association between variability in cB12 and candidate polymorphisms and genes previously associated with B12 biomarker levels characterized in silico the mechanism linking the genetic variants and cB12 variability.We found the variability in cB12 and its constituents to be highly heritable (h2=55%–64%). The single nucleotide polymorphism rs291466 in HIBCH, previously associated with variation in MMA, was significantly associated with cB12 (R2=5%, P=5E-04). Furthermore, variants in MTRR, MMAB and MUT, underlying inborn errors of B12 metabolism, were nominally associated with variation in cB12. Pathway accompanied by expression quantitative trait loci analysis revealed that HIBCH rs291466 influences the concentration of MMA via the valine degradation pathway.Our study provides etiological insight into how B12 deficiency can manifest into impaired mitochondrial function through perturbations in mitochondrial “fuel” usage.